Toll-like Receptors as Pro-Thrombotic Drivers in Viral Infections: A Narrative Review - Benjamin Panzer; Christoph W. Kopp; Christoph Neumayer; Renate Koppensteiner; Alicja Jozkowicz; Michael Poledniczek; Thomas Gremmel; Bernd Jilma; Patricia P. Wadowski (Cells, 2023)
Toll-like receptors (TLRs) have a critical role in the pathogenesis and disease course of viral infections. The induced pro-inflammatory responses result in the disturbance of the endovascular surface layer and impair vascular homeostasis. The injury of the vessel wall further promotes pro-thrombotic and pro-coagulatory processes, eventually leading to micro-vessel plugging and tissue necrosis. Moreover, TLRs have a direct role in the sensing of viruses and platelet activation. TLR-mediated upregulation of von Willebrand factor release and neutrophil, as well as macrophage extra-cellular trap formation, further contribute to (micro-) thrombotic processes during inflammation. The following review focuses on TLR signaling pathways of TLRs expressed in humans provoking pro-thrombotic responses, which determine patient outcome during viral infections, especially in those with cardiovascular diseases.